Macasiamenene V, a New Stilbenoid from the Leaves of Macaranga inermis - Muhammad Fajar Aldin, .- (Korean Society of Pharmacognosy, 2021)
One new compound, macasiamenene V (1), and two known stilbenes (2-3) were isolated from Macaranga inermis Pax & K.Hoffm leaves. The structure of 1 was fully assigned based on the information on high-resolution MS and (1D, 2D) NMR spectra. The cytotoxic of compounds 1-3 was evaluated against 4T1 and HeLa cells. Compounds 2-3 showed high activity against HeLa cells with an IC50 value of 1.09 and 0.88 ㎍/mL, respectively.